The best possible self‐intervention as a viable public health tool for the prevention of type 2 diabetes: A reflexive thematic analysis of public experience and engagement - Benjamin Gibson; Kanayo Umeh; Ian Davies; Lisa Newson (Wiley, 2021)
Abstract Background Public health initiatives seek to modify lifestyle behaviours associated with risk (e.g., diet, exercise, and smoking), but underpinning psychological and affective processes must also be considered to maximize success. Objective This study aimed to qualitatively assess how participants engaged with and utilized the best possible self (BPS)‐intervention specifically as a type 2 diabetes (T2D) prevention tool. Design and Methods Fourteen participants engaged with a tailored BPS intervention. Reflexive thematic analysis analysed accounts of participant's experiences and feasibility of use. Results All participants submitted evidence of engagement with the intervention. The analysis considered two main themes: Holistic Health and Control. The analysis highlighted several nuanced ways in which individuals conceptualized their health, set goals, and received affective benefits, offering insights into how people personalized a simple intervention to meet their health needs. Conclusions To our knowledge, this is the first study to tailor the BPS intervention as a public health application for the prevention of T2D. The intervention enabled users to identify their best possible selves in a way that encouraged T2D preventive behaviours. We propose that our tailored BPS intervention could be a flexible and brief tool to assist public health efforts in encouraging change to aid T2D prevention. Public Contribution The format, language and application of the BPS intervention were adapted in response to a public consultation group that developed a version specifically for application in this study.